Tunable electronic properties in bismuthene/2D silicon carbide van der Waals heterobilayer. (29th November 2019) - Sarker, Joy D.; Islam, Md. Sherajul; Ferdous, Naim; Sarker, Pantha P.; Bhuiyan, Ashraful G.; Makino, Takayuki; Hashimoto, Akihiro
Abstract: A comprehensive analysis of the structural and electronic properties of a novel 2D bismuthene and silicon carbide (SiC) van der Waals heterostructure is performed using first-principles calculation. The electronic structure of the proposed heterobilayer can be effectively tuned by changing the interlayer distance as well as upon the application of biaxial strain. The inclusion of spin–orbit coupling results in the splitting in the CB and VB with a greater reduction in the band gap. The calculated projected density of states and space-charge distribution near the CB and VB reveals the carrier confinement at the bismuthene layer only, indicating the prospect of 2D-SiC as a potential substrate for the realization of bismuthene-based heterostructure. Lower electron effective mass is computed, which dictates the higher electron mobility on the heterobilayer. These intriguing findings will manifest a new path for the realization of bismuthene-based high-speed nanoelectronic devices.